Host/guest complex of β-cyclodextrin/5-thia pentacene-14-one for photoinitiated polymerization of acrylamide in water - Balta, Demet Karaca; Arsu, Nergis (ELSEVIER SCIENCE SA, 2008)
beta-Cyclodextrin (beta-CD) was used to complex the photoinitiator, 5-thia pentacene-14-one (TX-A), yielding a water-soluble host/guest complex. IR, UV-Vis and fluorescence spectroscopy were employed to characterize complexed beta-CD/TX-A. Photoinitiated polymerization of acrylamide in water was achieved with beta-CD/TX-A in the presence of N-methyldiethanolamine (MDEA). Excellent polymerization yields were observed in air saturated solutions when MDEA was added. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anthracene; beta-Cycloclextrin; Singlet oxygen; Photopolymerization; Thioxanthone; FREE-RADICAL POLYMERIZATION; METHYL-METHACRYLATE; AQUEOUS PHOTOPOLYMERIZATION; BETA-CYCLODEXTRIN; INCLUSION; OXYGEN; Chemistry